Determinants of Carbon Disclosure: The Role of Sustainability Assurance, Board Independence, Institutional Ownership and Gross Domestic Product in Mining Companies Across Five ASEAN Countries - Annisa Annisa; Juniati Gunawan (DINASTI RESEARCH, 2026)
This study aims to analyze the effect of Sustainability Assurance, Board Independence, Institutional Ownership, and Gross Domestic Product on Carbon Disclosure in Mining Companies Across Five ASEAN Countries (Indonesia, Malaysia, Filipina, Singapura, Thailand). This research applies a quantitative approach using secondary data obtained from annual reports and sustainability reports during the period from 2022 to 2024. Sustainability Assurance and Carbon Disclosure are measured through content analysis based on ISAE 3000 and TCFD, while the hypotheses are tested using panel data regression with the Fixed Effect Model. The results show that Sustainability Assurance and Institutional Ownership have a positive and significant effect on Carbon Disclosure, while Board Independence and Gross Domestic Product have a positive but insignificant effect. This study recommends that companies improve the quality of carbon reporting and strengthen the reliability of sustainability information through more comprehensive assurance practices.